STUDYING THE CHEMICAL CONSTITUENTS OF THE ESSENTIAL OIL FROM HORSERADISHLEAVES (Scientific journal of the Fergana State University, 2025)
The composition of the essential oil of dry horseradish leaves grown in the Fergana region was studied using gas chromatography-mass spectrometry. According to the results of the study, 21 compounds were found in the essential oil of horseradish leaves, of which 15 compounds were identified, which makes up 94.58% of the total number of detected compounds. The essential oil contains nitriles, heterocyclic compounds, unsaturated hydrocarbons, aldehydes, and terpenoids. The main compounds of the essential oil are 3-butenenitrile (48.3%); 10-methyl-9-nonadecene (13.40%); (2R, 4S)-2,4-dimethyl-5-hexen-1-ol (9.95%); phenylacetaldehyde (4.6%); 1-(5(methyl-2-furanyl)-1-buten-3-one (3.6%); 1H-pyrrole (2.2%) and (-)-isocaryophyllene (2.1%) were found.